1993
DOI: 10.1007/bf00315397
|View full text |Cite
|
Sign up to set email alerts
|

Acetylator polymorphism in rheumatoid arthritis

Abstract: Acetylator phenotype has been determined with sulphamethazine (sulphadimidine) in 69 Spanish patients with rheumatoid arthritis (48 females), all of whom were on second line therapy, and in 96 age-matched normal controls (54 females). Thirty-two patients (46.4%) and 56 controls (58.3%) were classified as slow acetylators. On analysing separately the females in both groups, 37.5% of patients and 63% of controls were found to be slow acetylators. No difference was found in the males (patients 66.3% and controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
5
1
Order By: Relevance
“…Previous human epidemiological studies have suggested an association between rapid acetylator phenotype and colorectal cancer (Lang et al 1986;Ilett et al 1987;Wohlleb et al 1990), whereas a previous study from our laboratory (Kirlin et al 1991) and others (Roots et al 1989;Ladero et al 1991) did not find this association. Our data comparing NAT2 allelic frequencies showed virtually identical distributions of the M1, M2, M3, and WT alleles between the non-cancer and colorectal cancer groups.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous human epidemiological studies have suggested an association between rapid acetylator phenotype and colorectal cancer (Lang et al 1986;Ilett et al 1987;Wohlleb et al 1990), whereas a previous study from our laboratory (Kirlin et al 1991) and others (Roots et al 1989;Ladero et al 1991) did not find this association. Our data comparing NAT2 allelic frequencies showed virtually identical distributions of the M1, M2, M3, and WT alleles between the non-cancer and colorectal cancer groups.…”
Section: Discussioncontrasting
confidence: 60%
“…As the slow acetylator phenotype predominates in Caucasian populations, the excess of rapid acetylators among RA patients (55.7%) found in this study suggested a possible relation of the disease with this phenotype. Two other phenotyping studies, including a fewer number of patients, agreed with this preliminary conclusion [26,27]. However, genotyping methods have not definitely solved this issue.…”
Section: Rheumatoid Arthritis (Ra)supporting
confidence: 60%
“…Two of three reports on human colorectal cancer, (13,28,29) have found that rapid acetylators are overrepresented among cases as compared to controls. In this context, we have shown that the heterocyclic amines, which have been implicated as a risk factor in this disease, are poor substrates for N-acetylation in human liver; however, they readily undergo hepatic N-oxidation and subsequent N-glucuronidation (vide infra), resulting in conjugated N-hydroxy metabolites that can be transported to the colonic lumen, hydrolyzed by ,B-glucuronidases, and reabsorbed.…”
Section: Acetyltransferasesmentioning
confidence: 99%